Photoperiod_Dyrad - Hawley, Kate; Rosten, Carolyn; Christensen, Guttorm; Lucas, Martyn (Dryad Digital Repository, 2017)
Tracking data of 23 individual Arctic charr, from Lake Ellasjøen, Bear Island, Norway. Data is derived by biotelemetry from Sep 2009- Aug 2010.